Identidad ambiental, actitud y comportamiento de conservación de agua en una comunidad alto-andina del Perú - Carbajal, Daniel (2020)
We investigated the environmental identity, attitude and behaviour of water conservation in inhabitants of a high Andean community in Peru (N=211) in order to determine the relationships between them. We applied the environmental identity scale and the questionnaire on water conservation attitudes and behaviour and proceeded to measure their correlations. A direct relationship was found between environmental identity, attitude and water conservation behaviour. The most significant correlation is between identity and behaviour, while the correlations between identity and attitude, attitude and behaviour, are moderate. On the other hand, the dimensions of environmental identity show significant positive correlations with attitude, while behaviour shows significant correlations with self-identification, positive emotions and the relevance of identity and ideology. Our findings indicate that environmental identity has a relationship with water conservation attitude. It was observed that, identity and/or connection with nature motivates people to protect and act in favour of it. Finally, the implications of pro-environmental behaviour on environmental identity and attitude to water conservation are discussed.